STUDIES ON AGE, GROWTH AND GEAR SELECTIVITY OF CIRRHINUS MRIGALA (HAMILTON) FROM RIHAND RESERVOIR, UTTAR PRADESH - Desai, V R; Shrivastava, N P (Indian Journal of Fisheries, 2011)
Age and growth study of Cirrhinus mrigala (Hamilton) from Rihand reservoir (U. P.), indicated that fishattained 210,384,514,602 and 695 mm in total length during 1 to 5 years of age respectively. Its growthwas poor in the reservoir with inadequacy of its food. Its fishery was lean only because the species wasnot exploited fully due to selective mode of fishing using gill nets of bigger meshes only. Action planis therefore required for developing its fishery and catching more Mrigal with gill nets of 45 - 90 mmbar to increase fish yield of Rihand reservoir.